KOMUNIKASI KULTURAL ANTAR UMAT BERAGAMA DALAM PERSPEKTIF MAQASHID SYARIAH (STUDI KEARIFAN LOKAL PELA GANDONG) - Marwing, Anita (Al AHKAM: Jurnal Kajian Ilmu Hukum dan Syariah, 2015)
This article aim at explaining the inter relation between local wisdomof pela gandongand cultural communications and also cultural communications of pela gandong based on theperspective maqasid syariah. The problem in this article is studied by using maqasid syariah as abasis for theory in studying local wisdom of pel gandong exist in Ambon. The result of thisstudy indicate that pela gandong besides having a meaning of tying also bear communicationspattern from two communities. This matter is shown with the quality of genetic relationshipbetween different citizen of community with call, the naming of greeting basudara (brothers).As cultural communication, pela gandong born from under, local wisdom of pela gandong havelinked relationship of human which in character as a human also and do not limit byvariousrules and normative limitation but as compliance and awareness and respect at ancestorsafter all pela gandong represent maximal masterpieces from all ancestor of Ambon - LeaseMaluku and formed from the way of thinking and behave from society when they respond theproblems of arising around them. Besides, pela gandong is suitable to maqasid syariah. Thismatter can be seen that target of law or declaring of law that was degraded by Allah is for thebenefit of mankind. Of that account, maqasid syariah can be told as benefit âdelivering all kindof benefit or refuse all damage possibilityâ. This matter in line with existence of local wisdomof pela gandong recognized to society of Ambon with aim at creating peace in interfaith whichis symbolized with brotherhood (sister and brother). With existence of pela gandong, it appeartolerance in religion to be able to produce well-balanced cooperation among religionpeople insocial activity, economic, defense, security, environment, etc. Besides, demage of which canmeance soul, slan, property and mind can be avoided by the existence of pela gandong.